2000
DOI: 10.1007/s003600050002
|View full text |Cite
|
Sign up to set email alerts
|

Ionic currents in cardiac myocytes of squid, Alloteuthis subulata

Abstract: This paper provides the first study of voltage-sensitive membrane currents present in heart myocytes from cephalopods. Whole cell patch clamp recordings have revealed six different ionic currents in myocytes freshly dissociated from squid cardiac tissues (branchial and systemic hearts). Three types of outward potassium currents were identified: first, a transient outward voltage-activated A-current (IA), blocked by 4-aminopyridine, and inactivated by holding the cells at a potential of -40 mV; second, an outwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…However, I K fast was more sensitive in clam than in oyster or in mussel. I K fast was inhibited by 4-AP, in agreement with data reported in many other species (Ö dblom et al 2000;Pennec et al 2004;Tseng et al 1987). Then TEA and 4-AP could be used to separate the fast and the delayed potassium currents in clam cardiomyocytes.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…However, I K fast was more sensitive in clam than in oyster or in mussel. I K fast was inhibited by 4-AP, in agreement with data reported in many other species (Ö dblom et al 2000;Pennec et al 2004;Tseng et al 1987). Then TEA and 4-AP could be used to separate the fast and the delayed potassium currents in clam cardiomyocytes.…”
Section: Discussionsupporting
confidence: 88%
“…Such a calcium current, classically observed in vertebrate cardiac tissue (Hagiwara et al 1988) has been identified in other molluscs (Curtis et al 1999;Ö dblom et al 2000;Pennec et al 2004). L-type channel, in molluscs as in lower vertebrates, is thought to be the primary pathway for Ca 2?…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…More recently, two types of potassium channels and also two types of calcium channels were characterized in the heart of the same species. Three major potassium currents were identified in a preliminary report in the squid Loligo forbesii (Ödblom and Williamson, 1995), followed more recently by another species, Allotheutis subulata (Ödblom et al, 2000): a fast inactivating current that is inhibited by 4-amino pyridine (4-AP), a delayed outward rectified current that is inhibited by tetraethyl ammonium chloride (TEA), and a calciumactivated current that is inhibited by cobalt ions and apamin. Calcium and fast sodium channels were also found.…”
mentioning
confidence: 99%